2013
DOI: 10.1021/ja403232d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Patronite Form of Vanadium Sulfide on Graphitic Layer

Abstract: With the exploding interest in transition metal chalcogenides, sulfide minerals containing the dianion S2(2-), such as pyrite (FeS2), cattierite (CoS2), and vaesite (NiS2), have recently attracted much attention for potential applications in energy conversion and storage devices. However, the synthesis of the patronite structure (VS4, V(4+)(S2(2-))2) and its applications have not yet been clearly demonstrated because of experimental difficulties and the existence of nonstoichiometric phases. Herein, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
263
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 314 publications
(287 citation statements)
references
References 46 publications
21
263
2
Order By: Relevance
“…The V 2p spectra of VS 2 and VS 2 −Li 2 S 6 are shown in SI Appendix, Fig. S4A, in which two peaks located at 517.3 and 524.8 eV with an energy separation of 7.5 eV are attributed to the V 2p 3/2 and V 2p 1/2 spin-orbit levels of VS 2 (38). Upon contact with Li 2 S 6 , both peaks shift about 0.8 eV to 1.0 eV toward lower binding energy.…”
Section: Resultsmentioning
confidence: 99%
“…The V 2p spectra of VS 2 and VS 2 −Li 2 S 6 are shown in SI Appendix, Fig. S4A, in which two peaks located at 517.3 and 524.8 eV with an energy separation of 7.5 eV are attributed to the V 2p 3/2 and V 2p 1/2 spin-orbit levels of VS 2 (38). Upon contact with Li 2 S 6 , both peaks shift about 0.8 eV to 1.0 eV toward lower binding energy.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been suggested from DFT calculations that the material exhibits a band gap of ~1.0 eV. 12 The open channels in-between the chains offer potential sites for topotactic Li insertion. The detailed mechanism for the redox process however is not well understood.…”
Section: 9mentioning
confidence: 99%
“…VS 4 -reduced graphene oxide (rGO) powder was prepared using the synthesis procedure described in a previous paper. 12 Briefly, GO was prepared from natural graphite powder by the Hummer's Method. 27 The GO solution (5 mg/mL) was added to a mixture of sodium orthovanadate and thioacetamide to make a total volume of 120 mL.…”
mentioning
confidence: 99%
“…[11,29] Another emerging compound is VS 4 , which contains two S 2 2-dimers and has an unusual linear-chain structure. [31,33] However, the oxidation state of V remains the same in VS 2 and VS 4 . It is interesting to note that since its discovery in 1906 and despite the specification of crystallographic data in 1964, [34,35] the procedures for the synthesis of VS 4 in its pure form have been cumbersome.…”
Section: Introductionmentioning
confidence: 98%
“…A few recent reports have suggested that VS 4 can be obtained in its pure form by following a facile hydrothermal method mediated by graphene oxide (GO) or carbon nanotubes (CNTs) as active templates. [33,36] Both GO and CNTs provide the required nucleation path for the transformation of VS 2 into VS 4 . The template-mediated synthesis produces a VS 4 / reduced graphene oxide (RGO) hybrid, which shows some interesting electrochemical activities for energy-storage applications.…”
Section: Introductionmentioning
confidence: 99%